Analysis of different type of PWM for three phase power converter - Mekhilef, Saad; Rahim, N.A.; Karim, Z.A. (2000)
An analysis of the three-phase PWM power convener is presented. The simulation techniques which is an interfacing of the high level programming C++ and PSpice simulation packages in generating the switching pulses for the power converter is discussed. Three different type of PWM; sinusoidal PWM, triplen harmonics PWM and third harmonic injection PWM are generated from a micro-controller for testing the effectiveness of the circuit.